PEMANFAATAN LIMBAH AIR TEMPE MENJADI PUPUK ORGANIK CAIR (POC) SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DAN LINGKUNGAN - Dewi Amaliah Nafiati (Jurnal Berdaya Mandiri, 2025)
Tunon Village, Tegal City, is the center of the tempeh home industry which contributes significantly to the local economy. However, liquid waste produced from the tempe making process is often thrown away carelessly, causing environmental pollution in the form of water pollution and unpleasant odors. This waste contains nutrients such as nitrogen and phosphorus, which have the potential to be used as liquid organic fertilizer (POC). This community service is carried out to overcome the problem of environmental pollution from tempe water waste. Implementation methods include problem identification, outreach, training and mentoring to the PKK Women's Farmer Group (KWT). The results of the activity show the enthusiasm of the community in utilizing tempe waste into POC, which not only reduces environmental pollution but also provides additional economic value. The POC produced is environmentally friendly and can be used to increase soil fertility. This activity proves the effectiveness of the educational approach in empowering the community while preserving the environment. Keywords: Tempeh Wastewater, Liquid Organic Fertilizer, Community Empowerment